Відновлення акустичної інформації з відеозапису без аудіодоріжки - Альхатіб, Г. Д. (ХНУРЕ, 2024)
This paper considers the theoretical aspects of possibility of the appearance of an acoustic information leakage channel that is formed by analyzing the video stream on the video record. Therefore, the possibility of its appearance is a security risk and it is necessary to provide the means to protect the object of information activity from it.
Keywords: акустична інформація; відеозапис без аудіодоріжки